Efeitos da introdução dos genes opaco-2 e farináceo-2 na variedade de milho centralmex - Saraiva, Luiz Sérgio; de Almeida Filho, José (Revista Ceres, 2025)
The genes opaque-2 and floury-2 were independently incorpo- rated into the corn variety Centralmex, and their effects on S0-kernel weight, kernel density and protein and lysine content were noted. Both opaque-2 and floury-2 kernels weighed approximately 12% less than normal kernels, and both were less dense than normal kernels with opaque-2 kernels having the lowest density. There was enough variability in both characteristics, however, to suggest that both kernel weight and density could be improved in the opaque-2 and floury-2 through selection. On a dry weight basis there was no significant difference in protein content between kernel types. Opaque-Z kernels, however, had 100 and 25% more lysine than normal and floury-2 kernels respectively. On a percent protein basis opaque-2 also had the highest and normal kernels the lowest lysine levels.